2013
DOI: 10.5604/20831862.1059168
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Gene Polymorphisms With Athlete Status in Ukrainians

Abstract: Athletic performance is a polygenic trait influenced by both environmental and genetic factors.ObjectiveTo investigate individually and in combination the association of common gene polymorphisms with athlete status in Ukrainians.MethodsA total of 210 elite Ukrainian athletes (100 endurance-oriented and 110 power-orientated athletes) and 326 controls were genotyped for ACE I/D, HIF1A Pro582Ser, NOS3 –786 T/C, PPARA intron 7 G/C, PPARG Pro12Ala and PPARGC1B Ala203Pro gene polymorphisms, most of which were previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 23 publications
2
53
1
3
Order By: Relevance
“…highly elite (25.0%)). These results were replicated in three cohorts of 158 Polish power-orientated athletes [218], 208 Russian power-oriented athletes (122 weightlifters and 86 wrestlers) [219], and 110 Ukrainian power-oriented athletes [220], but not in 81 Israeli sprinters [221]. Furthermore, the 582Ser allele was significantly associated with an increased proportion of fast-twitch muscle fibers in m. vastus lateralis of all-round speed skaters [217].…”
Section: Hif1a 582ser Allelesupporting
confidence: 62%
See 2 more Smart Citations
“…highly elite (25.0%)). These results were replicated in three cohorts of 158 Polish power-orientated athletes [218], 208 Russian power-oriented athletes (122 weightlifters and 86 wrestlers) [219], and 110 Ukrainian power-oriented athletes [220], but not in 81 Israeli sprinters [221]. Furthermore, the 582Ser allele was significantly associated with an increased proportion of fast-twitch muscle fibers in m. vastus lateralis of all-round speed skaters [217].…”
Section: Hif1a 582ser Allelesupporting
confidence: 62%
“…In a study of Russian power-oriented athletes (n ¼ 260), the higher frequency (23.8% vs. 15.1%; P < 0.0001) of the PPARG 12Ala allele compared to 1073 controls has been reported [238]. These results were replicated in two studies involving 182 Polish strength athletes [239] and 110 Ukrainian power-oriented athletes [220].…”
Section: Pparg 12ala Allelementioning
confidence: 62%
See 1 more Smart Citation
“…Based on this algorithm, several studies have attempted to identify polygenic profiles that could determine the potential for becoming an elite athlete; [6][7][8][9][10][11] most of the studies indicated that elite athletes have higher TGSs than non-athletic controls. Recently, it was suggested that the TGS could be used as an additional tool for selecting appropriate athletic events.…”
Section: Page 5 Of 26mentioning
confidence: 99%
“…Numerous studies results favour for interaction of ACE gene I/D polymorphism with high sport achievements [16].…”
Section: Resultsmentioning
confidence: 99%